PERANCANGAN SISTEM PERMOHONAN DATA BERBASIS WEBSITE UNTUK MENINGKATKAN EFISIENSI LAYANAN PUBLIK DI INSTANSI BMKG WILAYAH III - Maedelien Simatupang; I Putu Gede Hendra Suputra (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
In the information era, the need for accurate meteorological, climatological, and geophysical data is growing, particularly among the public and related institutions. The Regional Meteorology, Climatology, and Geophysics Office III previously managed data requests manually, often facing delays and record-keeping errors. To address this, a web-based data request system was developed to improve service efficiency and transparency. The system development involved needs analysis through interviews and was tested with Black Box Testing to ensure each feature functioned correctly. Key features of the system include a monitoring dashboard, automated task distribution, and document management with an official number and Electronic Signature (TTE). Implementation results show that the system speeds up and simplifies data request management, reduces errors, and has a positive impact on BMKG Regional Office III and data users.